Girls of summer [compact disc, unabridged] - Thayer, Nancy, 1943- (Brilliance Audio, 2020)
Lisa Hudson feels more alive than she has in a long time after hiring hunky carpenter Mack Whitney to renovate her old Nantucket home. There's no denying the spark growing between them, despite the fact that Mack is ten years her junior. But her twentysomething children, Juliet and Theo, on the island for the summer, worry that the new relationship will only lead to Lisa's heartbreak.